The value of cos A is √(1 + x²)/ (1 - x²) /√1 + x
<h3>Trigonometric ratios</h3>
It is important to note that
sin A = opposite/ hypotenuse
cos A = adjacent/ hypotenuse
Then,
opposite = ![\sqrt{1} - x](https://tex.z-dn.net/?f=%5Csqrt%7B1%7D%20-%20x)
Hypotenuse = ![\sqrt{1} + x](https://tex.z-dn.net/?f=%5Csqrt%7B1%7D%20%2B%20x)
Let's find the adjacent side using the Pythagorean theroem
![(\sqrt{1} + x)^2 = (\sqrt{1 -x } )^2 + x^2](https://tex.z-dn.net/?f=%28%5Csqrt%7B1%7D%20%2B%20x%29%5E2%20%3D%20%28%5Csqrt%7B1%20-x%20%7D%20%29%5E2%20%2B%20x%5E2)
![1 + x^2 = 1 - x^2 + x^2](https://tex.z-dn.net/?f=1%20%2B%20x%5E2%20%3D%201%20-%20x%5E2%20%2B%20x%5E2)
![x = \sqrt{\frac{1 + x^2}{1 -x^2} }](https://tex.z-dn.net/?f=x%20%3D%20%5Csqrt%7B%5Cfrac%7B1%20%2B%20x%5E2%7D%7B1%20-x%5E2%7D%20%7D)
cos A = x/hypotenuse
![cos A = \frac{\sqrt{\frac{1+x^2}{1 -x^2} } }{\sqrt{1} +x}](https://tex.z-dn.net/?f=cos%20A%20%3D%20%5Cfrac%7B%5Csqrt%7B%5Cfrac%7B1%2Bx%5E2%7D%7B1%20-x%5E2%7D%20%7D%20%7D%7B%5Csqrt%7B1%7D%20%2Bx%7D)
cos A = √(1 + x²)/ (1 - x²) /√1 + x
Thus, the value of cos A is √(1 + x²)/ (1 - x²) /√1 + x
Learn more about trigonometric identities here:
brainly.com/question/7331447
#SPJ1
Answer:
-12
Step-by-step explanation:
Evaluating each expression means to simplify the expression down to it's simplest form.
No on can explain it but it has a definition.